(untitled) (Research, Society and Development, 2022)
Introduction: The development of specific software with Serious Games (SG) is promising for use in physiotherapy. Objective: To develop and test the applicability of an SG for the balance training of hemiparetic patients after stroke. Methods: Hemiparetic stroke patients have evaluated pre and post-training in terms of functional mobility (Timed Up and Go Test), gait speed (10 meters), bilateral femoral quadriceps muscle strength (Hand-held Dynamometry), balance (Berg Balance Scale), and perception of self-efficacy (Self-efficacy questionnaire after stroke). For training, a system was developed consisting of a balance board with inertial sensors, a microcontroller system, and a computer system that executes a JS. Descriptive statistics were performed to characterize the individuals. After verifying the normality of the data, the differences between the pre-test and the post-test were verified using the paired Student’s t-test and the Wilcoxon test using a significance level of p <0.05. Results: Seven individuals completed the training. All variables showed statistically significant differences (p <0.05), except for the strength of the quadriceps muscle on the non-paretic side. Conclusion: The development of GS represents a viable and very promising possibility in this field. Studies with a larger number of individuals, comparing this approach with conventional ones, as well as the involvement of a control group will expand the understanding of the therapeutic potentials of this resource.